Validation of the Arabic Version of the Movement Disorder Society‐Unified Parkinson's Disease Rating Scale. Issue 4 (26th February 2022) - Khalil, Hanan; Aldaajani, Zakiyah F.; Aldughmi, Mayis; Al‐Sharman, Alham; Mohammad, Tareq; Mehanna, Raja; El‐Jaafary, Shaimaa I.; Dahshan, Ahmed; Ben Djebara, Mouna; Kamel, Walaa A.; Amer, Hanan A.; Farghal, Mohammed; et al.
Abstract: Background: The Movement Disorder Society‐Unified Parkinson's Disease Rating Scale (MDS‐UPDRS) has become the gold standard for evaluating different domains in Parkinson's disease (PD), and it is commonly used in clinical practice, research, and clinical trials. Objectives: The objectives are to validate the Arabic‐translated version of the MDS‐UPDRS and to assess its factor structure compared with the English version. Methods: The study was carried out in three phases: first, the English version of the MDS‐UPDRS was translated into Arabic and subsequently back‐translated into English by independent translation team; second, cognitive pretesting of selected items was performed; third, the Arabic version was tested in over 400 native Arabic‐speaking PD patients. The psychometric properties of the translated version were analyzed using confirmatory factor analysis (CFA) as well as exploratory factor analysis (EFA). Results: The factor structure of the Arabic version was consistent with that of the English version based on the high CFIs for all four parts of the MDS‐UPDRS in the CFA (CFI ≥0.90), confirming its suitability for use in Arabic. Conclusions: The Arabic version of the MDS‐UPDRS has good construct validity in Arabic‐speaking patients with PD and has been thereby designated as an official MDS‐UPDRS version. The data collection methodology among Arabic‐speaking countries across two continents of Asia and Africa provides a roadmap for validating additional MDS rating scale initiatives and is strong evidence that underserved regions can be energically mobilized to promote efforts that apply to better clinical care, education, and research for PD. © 2022 International Parkinson and Movement Disorder Society